5.4: The Effects of 0.01% Atropine on Adult Myopes' Contrast Sensitivity. (26th August 2021) - Cheng, Ziyun; Mei, Jianhui; Cao, Suqi; Zhang, Ran; Zhou, Jiawei; Wang, Yuwen
Abstract : Purpose: Atropine at a low concentration is considered a safe and effective treatment to mitigate myopia progression. However, the potential unwanted side effects of administering atropine at a low dose on visual functions other than best corrected visual acuity has not been investigated. In this study, we investigate the short‐term (12, 16, and 20 h) and long‐term (1, 2, and 4 weeks) effects of 0.01% atropine (i.e., 0.1 mg/ml) on contrast sensitivity (CS) in patients with myopia. Methods: Thirty adults (23.33 ± 2.93 years old) with myopia between −1.00 and −6.00 diopters (D), astigmatism of −1.50 D or less, and anisometropia of 1.00 D or less, participated in this prospective, masked, placebo‐controlled, randomized study. The participants were randomly assigned to receive 0.01% atropine or polyvinyl alcohol eye drops once nightly to both eyes for four weeks. CS was measured binocularly at baseline and 12, 16, 20 h, 1, 2, and 4 weeks after the first use of the eye drops. Results: There was no statistically significant differences of CS found between atropine and placebo‐controlled groups in both short‐term and long‐term. There was no statistically significant interaction effect found between the time and group. Conclusion: We demonstrated no significant deleterious effect of 0.01% atropine on adult myopes' CS.